2008
DOI: 10.2172/922542
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Ancillary Load Reduction Project Close-Out Report: An Overview of the Task and a Compilation of the Research Results

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Executive Services and Communications Directorate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Thermal loads, such as those used for heating, ventilation, & air conditioning (HVAC) of the passenger compartment, and for the electric motor and battery package cooling, represent the most significant auxiliary loads for light-duty vehicles [1]. It has been estimated that, in the United States, about 7 billion gallons of fuel is consumed per year just to power the air conditioning (A/C) system for light-duty vehicles [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal loads, such as those used for heating, ventilation, & air conditioning (HVAC) of the passenger compartment, and for the electric motor and battery package cooling, represent the most significant auxiliary loads for light-duty vehicles [1]. It has been estimated that, in the United States, about 7 billion gallons of fuel is consumed per year just to power the air conditioning (A/C) system for light-duty vehicles [1].…”
Section: Introductionmentioning
confidence: 99%
“…These improvements have the potential to reduce HVAC losses by about 30%. 36 Electrifi cation of power steering and other auxiliary components present signifi cant additional opportunities for reducing energy loads. Historically, auxiliary components are driven by mechanical accessory drives that are much less effi cient than electrical accessory drives.…”
Section: Auxiliary Loadsmentioning
confidence: 99%
“…The vehicle queuing process is explicitly modeled by the shockwave profile model with consideration of vehicle deceleration and acceleration to provide a green window for eco-vehicle speed trajectory planning. For light-duty HEVs with relatively small batteries, air conditioning of the passenger compartment is the primary thermal load in summer, which represents the most significant auxiliary load on the electric battery [7]. It has been found that the energy efficiency of the A/C system is dependent on vehicle speed [8].…”
Section: Introductionmentioning
confidence: 99%